Keputusan Pembelian Smartphone Berdasarkan Customer Relationsip Management dan Marketing Mix Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Dharma Andalas Padang - Yendra, Nofri; Rosa, Yenni Del; Rahman, Ardi Abdillah; Rismanda, Rachyta (Universitas Dharma Andalas, 2024)
The purpose of the study was to determine the effect of customer relationship management and marketing mix on smartphone purchasing decisions of students of the Faculty of Economics, Dharma Andalas University Padang. The research sample of 281 people was determined using the Slovin formula with proportional sampling technique . The data collection method uses a questionnaire with the dependent variable of purchasing decisions (Y), and the independent variable customer relationship management consists of customer orientation variables (X1), knowledge management (X2), organization (X3), technology (X4) and marketing mix consists of product variables (X5), price (X6), place (X7), promotion (X8), people (X9), physical evidence (X10) and process (X11). Partial hypothesis testing shows that all customer relationship management variables have a significant positive effect on smartphone purchasing decisions except the variables of organization, people, physical evidence and process have a negative effect. then all marketing mix variables have a significant positive effect on smartphone purchasing decisions except the variables of place, people and process have a significant negative effect. Simultaneous hypothesis testing shows that all customer relationship management and marketing mix variables have a significant positive effect on smartphone purchasing decisions of students of the Faculty of Economics, Dharma Andalas University Padang. Abstrak Tujuan penelitian untuk mengetahui pengaruh customer relationship management dan marketing mix terhadap keputusan pembelian smartphone mahasiswa Fakultas Ekonomi Universitas Dharma Andalas Padang. Sampel penelitian sebanyak 281 orang ditentukan memakai rumus Slovin dengan teknik sampling alokasi proportional sampling. Metode pengumpulan data menggunakan angket. Variabel terikat keputusan pembelian (Y), variabel bebas customer relationship management terdiri dari variabel orientasi pelanggan (X1), manajemen pengetahuan (X2), organisasi (X3), teknologi (X4) dan marketing mix terdiri dari variabel produk (X5), harga (X6), tempat (X7), promosi (X8), orang (X9), bukti fisik (X10) dan proses (X11). Uji hipotesis parsial menunjukkan bahwa semua variabel customer relationship management berpengaruh positif signifikan terhadap keputusan pembelian smartphone kecuali variabel organisasi, orang, bukti fisik dan proses berpengaruh negatif. Juga semua variabel marketing mix berpengaruh positif signifikan terhadap keputusan pembelian smartphone kecuali variabel tempat, orang dan proses berpengaruh negatif signifikan. Uji hipotesis secara simultan pada tingkat signifikansi 5% menunjukkan semua variabel customer relationship management dan marketing mix berpengaruh positif signifikan terhadap keputusan pembelian smartphone mahasiswa Fakultas Ekonomi Universitas Dharma Andalas Padang